Sustainable Mangrove Tourism: Economic Valuation and Participation in Sinjai - Sri Wahyuni; Muhammad Najib Kasim; Nurul Izzah (Universitas Ahmad Dahlan, 2024)
Introduction: Mangrove Forest is one of the tourist attractions that has the benefits of beauty, uniqueness and significant economic value for the people of Tongke - Tongke village, Sinjai Regency. The purpose of this study was to calculate the economic benefits of mangrove forests using the Individual Travel Cost Method. Data were obtained through a visitor survey with a total of 22 observations. There are 6 variables used in this study, namely Number of Visits as the dependent variable and Travel Cost, Distance, Age, Education, and Occupation as independent variables. The results of this study explain how these variables affect a person's decision to travel and how much influence it has on the number of tourist visits made . Objective: This study aims to identify the form of community participation and economic benefits of mangrove forests using the travel cost method from an Islamic economic perspective. Methodology: This study uses the ITCM (Individual Travel Cost Method) analysis technique, which is a travel cost analysis method using survey data from individual visitors in statistical analysis. Findings: Based on the results of this study, it was found that the tongke-tongke village community participated in the development of mangrove forests from an economic and social perspective, the existence of a mangrove forest tourism village was initiated by the surrounding community because it was built on the work and self-help of the local community, so that this mangrove forest is community-based, and this is one of its characteristics that distinguishes the existence of mangrove forests in other areas that exist as engineering results of government policies that have a large economic benefit value for visitors, this can be seen from the value of economic benefits obtained for one year which amounted to Rp. 176,307,689, from an Islamic economic perspective the existence of this mangrove forest is able to provide mashlahah for the ecosystem around the mangrove debt area. 176,307,689, from an Islamic economic perspective the existence of this mangrove forest is able to provide mashlahah for the ecosystem around the mangrove debt area. Paper Type: Research Article Keywords: Participation; Mangrove Forest; Nature Tourism; Travel Cost; Islamic Economic Perspective.